Profile of newborns with retinopathy of prematurity in a University Hospital in Espírito Santo state, Brazil (Brazilian Journal of Health Research, 2024)
Introduction: The etiology of Retinopathy of Prematurity (ROP) is multifactorial, with varying degrees of involvement, and should be diagnosed early in neonates as it can progress to partial or total loss of vision. Objectives: To identify the profile of patients with ROP in the high-risk newborn follow-up outpatient clinic. Method: Cross-sectional, retrospective study, analyzing patients from the follow-up program of newborns, from October 2020 to September 2021, diagnosed with ROP. Results: Of the 132 patients, 116 were premature, and 97 met the criteria for retinal mapping. Among these, 15 cases of ROP were identified (11.4% of the total, 15.5% of the mapped patients). Of the patients with ROP, prenatal care was inadequate in 80%, extremely low birth weight accounted for 43.8%, and very low birth weight for 33.3% of cases. Extremely premature was 53.3%. Average medical discharge was 100 days (60% for more than 60 days). Fourteen patients required ventilatory support (1 patient had no information), with 53.3% more than 28 days. Eleven patients required invasive ventilation, with an average duration of 27 days (±26.1). Stage 1 ROP was present in 40%, stage 2 in 33.3%, and stage 3 in 26.7%, with 6.7% having plus disease. Photocoagulation was performed in 26.7%, and complete regression occurred in 80%. Conclusion: The study identified a significant number of ROP cases among patients, particularly highlighting those without complete prenatal care, with extremely or very low birth weight, and extremely premature infants, with prolonged hospital stays.
Keywords: Retinopathy of Prematurity; Ambulatory Care; Intensive Care Neonatal